(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
A new approach to print non-assembly mechanisms with reduced joint clearance is used to create an additive manufactured finger prosthesis. Like other additive manufacturing methods, Fused Layer Modeling (FLM) requires a sufficient clearance between parts to archive moveable non-assembly mechanisms. A two-material design and a heat treatment allowed improving the accuracy of the movement beyond the printing limitations. It was shown that a functional finger prosthesis can be produced using this technique.